2007
DOI: 10.1007/s00182-007-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

Congestion games revisited

Abstract: Nash equilibrium existence, Potential game, Congestion game, Additive aggregation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…The proof of the theorem, which is relegated to the Appendix, utilizes the ingenious idea of Rosenthal (1973) to show that our game of social interactions is a potential game studied in Monderer and Shapley (1996) (see also Kukushkin (2007)). Note that Assumption A1 is vacuous when X is a finite set.…”
Section: The Model and Resultsmentioning
confidence: 99%
“…The proof of the theorem, which is relegated to the Appendix, utilizes the ingenious idea of Rosenthal (1973) to show that our game of social interactions is a potential game studied in Monderer and Shapley (1996) (see also Kukushkin (2007)). Note that Assumption A1 is vacuous when X is a finite set.…”
Section: The Model and Resultsmentioning
confidence: 99%
“…An alternative, more transparent proof was given in Voorneveld et al (1999, Theorem 3.3). Kukushkin (2007) introduced games with structured utilities, in a sense, "dual" to congestion games; the players there do not choose which facilities to use, only how to use facilities from a fixed list. The idea of such a structure of utility functions can be traced back to Germeier and Vatel' (1974), although the local utilities in that paper were aggregated with the minimum function.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of such a structure of utility functions can be traced back to Germeier and Vatel' (1974), although the local utilities in that paper were aggregated with the minimum function. Theorem 5 from Kukushkin (2007) showed that a strategic game admits an exact potential if and only if it can be represented as a game with structured utilities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations